2008
DOI: 10.1007/s00384-008-0597-7
|View full text |Cite
|
Sign up to set email alerts
|

D3 lymphadenectomy using a medial to lateral approach for curable right-sided colon cancer

Abstract: The findings indicate that a D3 lymphadenectomy using the MtL approach is a feasible and safe procedure for the treatment of curable right-sided colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
2
33
0
2
Order By: Relevance
“…37 another study shows that a D3 lymphadenectomy using a medial to lateral approach is a feasible and safe procedure for the treatment of curable right-sided colon cancer in both the open and laparoscopic surgery. 38 a move toward Cme with central vascular ligation has been proposed by other european centers, resulting in a marked improvement in the oncologic quality of the specimen produced 39 that does not increase the postoperative complication or mortality rates. 40 there are limitations to our study.…”
Section: Discussionmentioning
confidence: 98%
“…37 another study shows that a D3 lymphadenectomy using a medial to lateral approach is a feasible and safe procedure for the treatment of curable right-sided colon cancer in both the open and laparoscopic surgery. 38 a move toward Cme with central vascular ligation has been proposed by other european centers, resulting in a marked improvement in the oncologic quality of the specimen produced 39 that does not increase the postoperative complication or mortality rates. 40 there are limitations to our study.…”
Section: Discussionmentioning
confidence: 98%
“…The medial to lateral approach may be more aligned with the no-touch principle than the lateral to medial approach. Recently, some reports demonstrated that progress in laparoscopic techniques for colorectal cancer surgery has resulted in the development of a medial to lateral approach for D3 lymphadenectomy [21,22]. Compared with the classical lateral to medial approach, D3 lymphadenectomy using the medial to lateral has the advantage of abiding by the no-touch isolation technique for oncologic surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…The assistant uses two working ports at the opposite side of the trocars used by the operator. For right-sided lesions, detailed procedures are described in our previous study [9]. After identification of the ileocolic and middle colic vessels, the assistant grasps the mesentery of the two vessels and pulls in the cephalic and lateral directions.…”
Section: Methodsmentioning
confidence: 99%